2019
DOI: 10.31965/infokes.vol17.iss1.221
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Terapi Bekam Kering Terhadap Tekanan Darah Pada Ibu Preeklampsia Postpartum

Abstract: Preeklampsia selama kehamilan bisa menetap pada masa postpartum dan biasanya akan kembali normal pada minggu pertama postpartum. Angka kejadian preeklampsia atau hipertensi postpartum secara keseluruhan terjadi sekitar 57,1%. Teknik non farmakologis untuk mengatasi hipertensi telah dikembangkan, salah satunya adalah bekam kering sebagai pilihan menurunkan tekanan darah. Penelitian quasy experiment dengan non equivalent control group design. Lokasi penelitian di RSUD Dr. Saiful Anwar Malang. Waktu penelitian di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
1
0
0
1
Order By: Relevance
“…This research is in line with research conducted by Pratama, Rasni, and W (2018). In addition to this research, research conducted by Eliyana, Nooryanto, and Poeranto (2019) also showed a decrease in blood pressure in the group given dry cupping therapy as indicated by a p value of 0.004.…”
Section: Differences In Systolic and Diastolic Blood Pressure In Patients Who Were Given Neck Massage Therapy Using Vco And Dry Cuppingsupporting
confidence: 90%
“…This research is in line with research conducted by Pratama, Rasni, and W (2018). In addition to this research, research conducted by Eliyana, Nooryanto, and Poeranto (2019) also showed a decrease in blood pressure in the group given dry cupping therapy as indicated by a p value of 0.004.…”
Section: Differences In Systolic and Diastolic Blood Pressure In Patients Who Were Given Neck Massage Therapy Using Vco And Dry Cuppingsupporting
confidence: 90%
“…Eliyana, Y., Nooryanto, M., & Poeranto, S. (2019). Pengaruh Terapi Bekam Kering Terhadap Tekanan Darah Pada Ibu Preeklampsia Postpartum.…”
unclassified